2008
DOI: 10.1016/j.nuclphysa.2007.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Recent soft-core baryon–baryon interactions

Abstract: Recent results obtained with the extended-soft-core (ESC) interactions are presented. In a unified manner the ESC-model describes nucleon-nucleon (NN), hyperon-nucleon (YN), and hyperon-hyperon (YY), using (broken) SU F (3)-symmetry. In the ESC approach to baryon-baryon (BB) the dynamics is derived from (i) one-boson-exchanges (OBE), (ii) two-meson-exchanges (TME), and (iii) meson-pairexchanges (MPE). Special features are the inclusion of the axial-vector meson potentials, and a zero in the scalar-meson form-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Comparing our results at NLO with those at LO one notices that the former provides more attraction in the 1 S 0 partial wave but significantly less in the coupled 3 S 1 -3 D 1 partial wave. Indeed the contribution predicted at NLO for this state is also much smaller than the values suggested by the Jülich meson-exchange potentials and other phenomenological models [15,17,18,22]. We believe that this has to do with a characteristic feature of our EFT interactions that was already emphasized in Ref.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Comparing our results at NLO with those at LO one notices that the former provides more attraction in the 1 S 0 partial wave but significantly less in the coupled 3 S 1 -3 D 1 partial wave. Indeed the contribution predicted at NLO for this state is also much smaller than the values suggested by the Jülich meson-exchange potentials and other phenomenological models [15,17,18,22]. We believe that this has to do with a characteristic feature of our EFT interactions that was already emphasized in Ref.…”
Section: Resultsmentioning
confidence: 56%
“…Microscopic models of the YN interaction, fitted to ΛN and ΣN scattering data, often fail to produce a repulsive Σ -nuclear potential. Specifically, for models based on meson-exchange dynamics it is rather difficult to obtain such a repulsion as is witnessed by results of G-matrix calculations for various generations of the Nijmegen YN potential [15][16][17][18]. Only the most recent version [19] could overcome this difficulty [20,21] -but at the expense of a noticeable increase in the achieved χ 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical analyses have also suggested that a repulsive component in the Σ-nucleus potentials is needed to reproduce the observed spectra of (π − , K + ) reactions on nuclear targets [5][6][7]. This repulsion originates from the ΣN T = 3/2, 3 S 1 channel, of which state corresponds to a quark Pauli-forbidden state in the baryon-baryon system [8,9], and it is a candidate for the appearance of quark degrees of freedom in nuclear physics.…”
Section: Introductionmentioning
confidence: 99%